Country data on AMR in Mexico in the context of community-acquired respiratory tract infections: links between antibiotic susceptibility, local and international antibiotic prescribing guidelines, access to medicine and clinical outcome. (6th September 2022) - Torumkuney, Didem; de la Torre, Carlos; Langfeld, Karen; Lopez-Turrent, Norma Patricia; Ossaille Beltrame, Cristiana
Abstract: Background: Antimicrobial resistance (AMR) is one of the biggest threats to global public health. Selection of resistant bacteria is driven by inappropriate use of antibiotics, amongst other factors. COVID-19 may have exacerbated AMR due to unnecessary antibiotic prescribing. Country-level knowledge is needed to understand options for action. Objectives: To review AMR in Mexico and initiatives addressing it. Identifying any areas where more information is required will provide a call to action to minimize any further rises in AMR and to improve patient outcomes. Methods: National AMR initiatives in Mexico, antibiotic use and prescribing, and availability of susceptibility data, particularly the key community-acquired respiratory tract infection (CA-RTI) pathogens Streptococcus pneumoniae and Haemophilus influenzae, were identified. National and international antibiotic prescribing guidelines commonly used in Mexico for specific CA-RTIs (community-acquired pneumonia, acute otitis media and acute bacterial rhinosinusitis) were also reviewed, along with local antibiotic availability. Insights from a local clinician were sought to contextualize this information. Conclusions: The Mexican national AMR strategy was published in 2018. This comprised similar objectives to the Global Action Plan from the World Health Assembly (2015) and was compulsory, requiring full compliance from members of the National Health System. Historically, antibiotic consumption in Mexico has been high, however, between 2000 and 2015, consumption fell, in sharp contrast to the majority of countries. Mexico lacks a national surveillance network for AMR, however there are several ongoing global surveillance studies providing local antibiotic susceptibility data. International and local antibiotic prescribing guidelines for CA-RTIs are used. A more standardized inclusive approach in developing local guidelines, using up-to-date local surveillance data of isolates from community-acquired infections, could make guideline use more locally relevant. This would pave the way for a higher level of appropriate antibiotic prescribing and improved adherence. This would, in turn, potentially limit AMR development in Mexico and improve patient outcomes.